2011
DOI: 10.1128/jcm.02390-10
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Prospective Clinical Evaluation of Respiratory Samples from Subjects at Risk for Pneumocystis jirovecii Infection by Use of a Commercial Real-Time PCR Assay

Abstract: Pneumocystis jirovecii pneumonia (PCP) is a common opportunistic infection. Microscopic diagnosis, including diagnosis using the Merifluor-Pneumocystis direct fluorescent antigen (MP-DFA) test, has limitations.Real-time PCR may assist in diagnosis, but no commercially validated real-time PCR assay has been available to date. MycAssay Pneumocystis is a commercial assay that targets the P. jirovecii mitochondrial large subunit (analytical detection limit, <3.5 copies/l of sample). A multicenter trial recruited 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 35 publications
(44 reference statements)
4
42
0
4
Order By: Relevance
“…Previous studies comparing real-time PCR assays to microscopy for the detection of P. jirovecii in respiratory specimens have also noted that substantial numbers of samples were positive by realtime PCR but negative by microscopy (2,7,9,13,15,19). Together with these studies, our results suggest that real-time PCR is more sensitive than microscopy for detecting P. jirovecii in BAL specimens.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Previous studies comparing real-time PCR assays to microscopy for the detection of P. jirovecii in respiratory specimens have also noted that substantial numbers of samples were positive by realtime PCR but negative by microscopy (2,7,9,13,15,19). Together with these studies, our results suggest that real-time PCR is more sensitive than microscopy for detecting P. jirovecii in BAL specimens.…”
Section: Resultssupporting
confidence: 76%
“…Previous studies have suggested that in some individuals P. jirovecii may colonize lung tissue without causing infection. Consequently, positive results, especially those with high C T values, must be interpreted in the context of patient symptoms in order to be able to distinguish colonization from infection (1,5,7,8,15,19). Likewise, negative results could be the result of insufficient sampling, resulting in a less than detectable number of P. jirovecii cells in the BAL specimen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations